Dipeptide Repeat Pathology in C9orf72-ALS Is Associated with Redox, Mitochondrial and NRF2 Pathway Imbalance - José Jiménez-Villegas; Janine Kirby; Ana Mata; Susana Cadenas; Martin R. Turner; Andrea Malaspina; Pamela J. Shaw; Antonio Cuadrado; Ana I. Rojo (MDPI AG, 2022)
The hexanucleotide expansion of the C9orf72 gene is found in 40% of familial amyotrophic lateral sclerosis (ALS) patients. This genetic alteration has been connected with impaired management of reactive oxygen species. In this study, we conducted targeted transcriptional profiling in leukocytes from C9orf72 patients and control subjects by examining the mRNA levels of 84 redox-related genes. The expression of ten redox genes was altered in samples from C9orf72 ALS patients compared to healthy controls. Considering that Nuclear factor erythroid 2-Related Factor 2 (NRF2) modulates the expression of a wide range of redox genes, we further investigated its status on an in vitro model of dipeptide repeat (DPR) toxicity. This model mimics the gain of function, toxic mechanisms attributed to C9orf72 pathology. We found that exposure to DPRs increased superoxide levels and reduced mitochondrial potential as well as cell survival. Importantly, cells overexpressing DPRs exhibited reduced protein levels of NRF2 and its target genes upon inhibition of the proteasome or its canonical repressor, the E3 ligase adapter KEAP1. However, NRF2 activation was sufficient to recover cell viability and redox homeostasis. This study identifies NRF2 as a putative target in precision medicine for the therapy of ALS patients harboring C9orf72 expansion repeats.